Antihypertensive activity and acute toxicity of turmeric (Curcuma longa L.) in L-NAME-induced hypertension animals - Patonah Hasimun; Yani Mulyani; Irma Yulianti (Institut Teknologi Bandung, 2022)
Hypertension is one of the significant risk factors for cardiovascular disease and can lead to complications. Uncontrolled hypertension can lead to vascular endothelial dysfunction and other complications of cardiovascular disease. This study aimed to determine the effect of turmeric rhizome (Curcuma longa L.) in extracts and the fractions on a hypertensive rat’s model induced by L-NAME 40 mg/kg for three weeks and an acute toxicity study of the extract. Antihypertensive research was performed on male Wistar rats utilizing non-invasive procedures. Turmeric extract at doses of 50, 100, and 200 mg/kg and its fraction of n-hexane, acetyl acetate, and ethanol at a dose of 25 mg/kg, respectively, were given daily per oral for three weeks to 2.5 mg/kg captopril. The systolic and diastolic blood pressure were measured at 0, 21, and 42 days after treatment and was calculated as mean arterial blood pressure (MAP). Acute toxicity testing refers to the OECD 420 Fixed-Dose method with several dosage levels, consists of 300, 2000, and 5000 mg/kg. The turmeric extract at doses of 50, 100, and 200 mg/kg and its fraction of n-hexane, acetyl acetate, and ethanol significantly reduced mean arterial blood pressure (p<0.05) compared to the control group. Acute administration of turmeric extracts up to a dose of 5000 mg/kg in test animals did not show any death. Turmeric and its components are considered to possess antihypertensive actions. Antihypertensive activity increased in a dose-dependent manner. Turmeric extract is categorized as being almost entirely non-toxic.